PERAN MEDIASI STRES KERJA ATAS PENGARUH BEBAN KERJA DAN KONFLIK KERJA TERHADAP KINERJA PEGAWAI (Studi pada Badan Kepegawaian Daerah Kota Pasuruan) - Devi Rohmaniah; Rahayu Puji Suci; Nasharuddin Mas (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
This study aims to obtain empirical evidence of the ability of workload and work conflict to affect employee performance, either directly or through the mediation of work stress. This type of research is quantitative with the SEM-SmartPLS method. Data were obtained through questionnaires which were distributed to 35 employees of the Pasuruan City Regional Civil Service Agency. The results obtained indicate that neither workload nor work conflict can affect employee performance, but both can influence work stress. The mediation role of work stress is very strong, because even though workload and work conflict are not able to directly affect employee performance, if through work stress mediation, both are able to influence the performance of employees of the Pasuruan City Regional Personnel Agency. This shows that work stress can act as a strong mediation.